Delimitación del concepto de riesgo psicosocial en el trabajo (Tema Central) - Sierra Hernáiz, Elisa (2021)
Nowadays one of the most important challenges at work is dealing with psychosocial risks at work. The main difficulties are the lack of a legal definition and the incorporation of mental health at work like as a more occupational risk. However, this situation can not mean that these risks are excluded from the policy for risk prevention in the workplace since it is about protecting fundamental rights at work, as the physical and psychological integrity or the right to not be discriminated. Until now the treatment of psychosocial risks at work in European Community law and in Spanish law has been carried out indirectly through the common preventive regulations for all risks, but mainly through the European and Spanish Technical Standards. The adoption of International Labour Organization Convention number 190 recognizes the right of everyone to a world of work free from violence and harassment, including gender-based violence and harassment. This ILO Convention it is a turning point that will force to regulate specifically these risks, which is a great step for its eradication in the field of labor relations. Therefore, in this article the concept of psychosocial risk is delimited as a health problem that must necessarily be integrated into the company’s preventive policy.